2021
DOI: 10.1177/09691413211061118
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy may be weak link in organised colorectal cancer screening programme with faecal immunochemical test

Abstract: Objective To evaluate the quality of colonoscopies performed after a positive faecal immunochemical test in the French colorectal cancer screening programme. Methods Retrospective analysis of all colonoscopies performed between 2015 and 2019 after a positive quantitative faecal immunochemical test in the population-based colorectal cancer screening programme organised in Alsace, part of the French programme. The following indicators were evaluated: annual colonoscopy volume, caecal intubation rate, adenoma det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Seventyfive full-length articles were assessed for inclusion and 23 studies were included in the final analysis [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41]. Sixteen studies reported SSPDR after only FIT testing [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34], three reported SSPDR on both FIT and FIT-DNA [35,36,37], and three studies reported SSPDR after only FIT-DNA testing (▶ Fig. 1) [38,39,40,41].…”
Section: Search Results and Population Characteristicsmentioning
confidence: 99%
“…Seventyfive full-length articles were assessed for inclusion and 23 studies were included in the final analysis [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41]. Sixteen studies reported SSPDR after only FIT testing [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34], three reported SSPDR on both FIT and FIT-DNA [35,36,37], and three studies reported SSPDR after only FIT-DNA testing (▶ Fig. 1) [38,39,40,41].…”
Section: Search Results and Population Characteristicsmentioning
confidence: 99%